Significance of Ligand-Anchored Polymers for Drug Targeting in the Treatment of Colonic Disorders - Pramila Chaubey; Munira Momin; Sujata Sawarkar (Frontiers Media S.A., 2020)
Treatment of a variety of bowel diseases like Crohn's disease, ulcerative colitis, colonic cancers, colonic pathologies, and systemic delivery of drugs at the target sites can be done with the help of targeted drug delivery technique. Conventional colon specific drug delivery systems lack specificity and release significant amount of drug prior reaching the target site. Hence, efficient drug delivery system that ensures effective release of the drug at the colon is still a sought after research arena. Ligand anchored therapy is a strong and effective approach to execute drug delivery in selective target cells, for both, diagnostic, as well as therapeutic reasons. Compared to the regular drugs, such ligand anchored therapy provides added benefit of minimum toxicity and few side effects. Discovery of overexpressed receptors on diseased cells, as compared to healthy cells led to the emergence of active drug targeting. Further, drug resistance constitutes one of the major reasons of the failure of chemotherapy and presents a major obstacle for the effective treatment. The reason behind drug resistance is exposure of pathological cells/pathogens to sub-therapeutic levels of drugs due lack of specificity of therapeutics. Active targeting, specifically taken up by the target cells, can warrant exposure of pathological cells/pathogens to high drug load at the target and sparing non-target cells hence minimal damage to normal cells and least chance of drug resistance. Many ligands like antibodies, aptamers, peptides, folate, and transferrin have been discovered in the past few years. The design of nanocarriers can be incorporated with many different functions which enables functions like imaging and triggered intracellular drug release. The present review article focuses on advances in ligand anchored therapy and its significance on the progress of targeted nanocarriers. It will also establish novel concepts like multi-targeting and multi-functional nanocarriers for the treatment of colonic disorders.